Analisis Volatilitas Harga, Volatilitas Spillover, dan Tren Harga pada Komoditas Kopi di Sumatera Utara Sebelum dan Sesudah Liberalisasi Perdagangan - Sinurat, Elis Wahyuni (Universitas Dharmawangsa, 2025)
This study aims to analyze price volatility, volatility spillover, and price trends in coffee commodities in North Sumatra before and after trade liberalization. Employing a quantitative approach with the ARCH/GARCH model, this study utilizes coffee price data in logarithmic return form from 1990 to 2024. The estimation results indicate that after trade liberalization, coffee price volatility increased significantly, exhibiting more persistent characteristics. Furthermore, a volatility spillover effect from international coffee prices to local prices was identified, suggesting that the domestic market has become more influenced by global dynamics. Trend analysis also reveals that prior to liberalization, prices experienced a stable upward trend, whereas post-liberalization prices became more volatile with no clear long-term direction. This research contributes theoretically to the commodity pricing literature by highlighting the crucial role of liberalization in shaping market risk structures. The practical implication of this study emphasizes the need for risk mitigation policies at the farmer level and the strengthening of local coffee competitiveness in the global market.